Retinoic Acid signaling regulates Krt5 and Krt14 independently of stem cell markers in submandibular salivary gland epithelium - Abashev, Timur M. (Dev Dyn, 2017)
BACKGROUND: Retinoic Acid (RA), the active metabolite of Vitamin A, has been demonstrated to be important for growth and branching morphogenesis of mammalian embryonic salivary gland epithelium. However, it is not known whether RA functions directly within epithelial cells or in associated tissues that influence morphogenesis of salivary epithelium. Moreover, downstream targets of RA regulation have not been identified. RESULTS: Here we show that canonical RA signaling occurs in multiple tissues of embryonic mouse salivary glands, including epithelium, associated parasympathetic ganglion neurons, and non-neuronal mesenchyme. By culturing epithelium explants in isolation from other tissues we demonstrate that RA influences epithelium morphogenesis by direct action in that tissue. Moreover, we demonstrate that inhibition of RA signaling represses cell proliferation and expression of FGF10 signaling targets, and upregulates expression of basal epithelial keratins Krt5 and Krt14. Importantly, we show that the stem cell gene Kit is regulated inversely from Krt5/Krt14 by RA signaling. CONCLUSIONS: RA regulates Krt5 and Krt14 expression independently of stem cell character in developing salivary epithelium. RA, or chemical inhibitors of RA signaling, could potentially be used for modulating growth and differentiation of epithelial stem cells for the purpose of re-populating damaged glands or generating bioengineered organs.